Strategic change and renewal - HUY, Quy N. (Institutional Knowledge at Singapore Management University, 2021)
Strategic change and renewal represent central concerns in strategic management. Despite many works on this topic, the body of knowledge remains fragmented. Our review of this literature suggests that research tends to focus narrowly on particular phases of strategic change, specific change actors in change process, and specific theoretical lenses. We highlight some important yet underexplored areas for future research. Finally, we argue how a more integrative approach could provide more textured insights and a deeper understanding of strategic change and renewal.